PENGARUH PROFITABILITAS SOLVABILITAS TERHADAP KEBIJAKAN DIVIDEN - Kurniasari, Erni; Listiawati, Listiawati; Siswandi, Siswandi (JAB (Jurnal Akuntansi & Bisnis), 2020)
ABSTRACTÂ This research aims to determine the influence of Profitability and Solvency on Dividend Policy partially and simultaneously. The population in this study were food and beverage sub sector manufacturing companies listed on the Indonesian Exchange during the period 2014-2018 and the sample used were seven companies based on the purposive sampling method. The results of the research show partially that Profitability has a significant effect on Dividend Policy as evidence by t-count of 3,842 greater than t-table of 2,035 and a significance value of 0,01 less than 0,05 while Solvency has no significant effect on Dividend Policy as evidence by t-count of -0.234 is greater than t-table of -2,035 and a significance value of 0,817 is greater than 0,05. Simultaneously Profitability and Solvency affect the dividend policy with the effect of 31,6% while 68,4% is influenced by other variables not examined.Â Keywords : Profitability, Solvency, Dividend Policy